(3Md GdQehR heaGJjM GdcfhRs - (3YHO GdSdGe Hf CMeO Hf ZGfe GdfGHdSj GdebOSj, YR GdOjf,J (B678 (3g` s
(3ChdgG (B:s
(3hHYO adeG cGfJ GdeYGfi LhGgQ hGdCdaGX CUOGagG hGdMce eYGOf hGdbdhH CgOGagG hEfi QCjJ cKjQ ef GdCdaGX bO EQJHc ai CZeGVgG cKjQ ef Cgd GdGYJQGV s
(3BNQgG (B:s
(3age Edjc hSjdJi jG SjOi EdG hUdJ MHGdge HMHGdi hGNjHI GdGeGd Gf CbUjJfi Yf HGHge jG NjHI GdGeGd Je GdcJGH HMeO Gddg JYGdi hYhfg hMSf Jhajbg s
(3HBNQg bUjOI dYdgG ddeDda ChdgG (B:s
(3HdZ ebGHdIs
(3jGSGOI gLQhG ef aVdce RhQhG ae eMHJce QjH hdG RhQ s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B355 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B5 - (3U (B223 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B5 - (3U (B571s
(3EjVGM Gdecfhf ddHZOGOi(B: (3L (B1 - (3U (B416s
Keywords: (3GdJUha hGdBOGH GdTQYjIs